Can rights be the underlying asset for Sukuk? the Malaysian experience. - Adam Sa'ad, Auwal (International Institute of Advanced Islamic Studies (IAIS) Malaysia, 2015)
Sukuk market has hitherto focused on issuances based on intangible underlying assets. Right (haqq) is intangible in nature which can in principle include government awards, goodwill, trademarks, receivables and other related rights as applied in the Islamic capital markets. This paper looks into the opinions of classical Muslim schools and scholars on whether or not these assets are acceptable assets for Sukuk. The paper incorporates analysis of the current applications of right as an underlying asset for Sukuk in Malaysia. The analysis includes a case study on Sukuk that uses right as an underlying asset, and raises some Shari’ah questions surrounding its applications. The study stipulates that right is an eligible asset for Sukuk transactions, because it is valuable and capable of ownership and possession. However, it is recommended that Sukuk based on government award should only be issued by government entities; private companies should not issue Sukuk based on government awards because it was based on iqta' principle and only the government has the right to grant its ownership to the general public.